Radiological Evaluation of Olfactory Fossa with Cone-Beam Computed Tomography - Ceren Özeren Keşkek; Emre Aytuğar (Stilus Optimus, 2021)
Objectives: The aim of this retrospective study was to evaluate the morphology of the olfactory fossa in the Turkish population using cone-beam computed tomography according to Keros classification and to investigate the effect of age, gender and nasal septum deviation on the olfactory fossa. Material and Methods: Olfactory fossa (OF) were analysed in coronal sections on cone-beam computed tomography images of 385 individuals. Nasal floor (NF), medial ethmoid roof point (MERP), cribriform plate (CP) heights, CP depth and width, OF width, lateral lamella-cribriform plate angle (LLCPA), and nasal septum deviation angle (NSDA) were measured. Keros and Gera classifications were made according to the measurements. Results: According to the Keros classification, 137 of 770 OFs were type I (17.8%), 554 (71.9%) were type II, and 79 (10.3%) were type III. The most common combination was Keros type II and Gera type II (45.6%). There was a positive correlation between CP depth and LLCP angle, NF, MERP and CP heights (P ≤ 0.05). NF, MERP, and CP heights, CP depth and LLCP angle were statistically significant differences according to Keros classification (P ≤ 0.05). Only the right LLCP angle showed a statistically significant difference according to the NSD sides (P = 0.014). Conclusions: The study shows that the lateral lamella-cribriform plate angle increases as the cribriform plate depth increases. This result suggests that it may moderate the risk during endoscopic sinus surgery. Also, according to the nasal septum deviation sides, the dimensions of the olfactory fossa did not change significantly, except for the lateral lamella-cribriform plate angle.